Esterifikasi Gliserol Produk Samping Biodiesel Dan Asam Asetat Menjadi Triacetin Menggunakan Katalis Fly Ash - Bettry Rifani; Zuchra Helwani; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is one of the alternative fuel which is made from triglycerides by transesterification alcohol processed and made 10% of byproducts is glycerol. One of the derivative products from glycerol is triacetin. Triacetin have many uses as additives in food and non food products. The research purpose is proccessed of glycerol as byproduct from biodiesel into triacetin using esterification method with catalyst fly ash on the variation concentration (1%, 2% and 3%) of catalyst, reactant mole ratio (1: 5, 1: 7 and 1: 9) and variation of esterification time (1, 2 and 3 hours) towards glycerol conversion. Data processing used the response surface methodology (RSM) and the experimental design used is central composite design. Fly ash catalyst characteristics such as acidity, crystallinity, and surface area increased after activation. The highest glycerol conversion obtained was 79.94% at a concentration of 3% catalyst, reactant mole ratio of 1: 9 and esterification time of 3 hours. Increasing concentrations of the catalyst, reactants mole ratio and time of esterification increase the conversion of glycerol. Esterification time is the most influential factor to increase conversion of glycerol in the production of triacetin.Keywords: catalyst, fly ash, esterification, glycerol, triacetin